2019
DOI: 10.13075/ijomeh.1896.01433
|View full text |Cite
|
Sign up to set email alerts
|

New ideas, old problems? Heated tobacco products – a systematic review

Abstract: Heated tobacco products (HTPs) are a form of nicotine delivery intended to provide an alternative to traditional cigarettes. The aim of this systematic review was to present the current state of knowledge on HTPs with an emphasis on the potential impact of HTP use on human health. During the preparation of this systematic review, the literature on HTPs available within Medline/PubMed, EMBASE, CINAHL, ScienceDirect, and Google Scholar was retrieved and examined. In the final review, 97 research papers were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 101 publications
(314 reference statements)
3
91
0
2
Order By: Relevance
“…Some basic facts on heat-not-burn tobacco products (e.g. iQOS), their regulation and data on their toxicity were reviewed previously 17 and more details can be found in the Supplementary material online .…”
Section: (Toxic) Compounds In Tobacco Cigarette Smoke E-cigarette Vamentioning
confidence: 99%
“…Some basic facts on heat-not-burn tobacco products (e.g. iQOS), their regulation and data on their toxicity were reviewed previously 17 and more details can be found in the Supplementary material online .…”
Section: (Toxic) Compounds In Tobacco Cigarette Smoke E-cigarette Vamentioning
confidence: 99%
“…Even if the association between the use of EATCs and adverse effects for human health is still under debate, there are several recent evidences of possible negative outcomes [13][14][15]. In addition to the possible adverse effects for active smokers of EATCs (the so-called vapers), experimental evidences demonstrate that the use of these devices worsen indoor air quality determining a typical passive exposure also called Environmental Electronic Vape (EEV) exposure [16][17][18]. The results of our previous researches [2,[19][20][21] highlighted that EEV exposure to particulate matter (PM) always occurs when e-cigs are used in indoor settings.…”
Section: Introductionmentioning
confidence: 99%
“…High exposure to HTP and cigarette advertising are consistent with the absence of a comprehensive advertising ban on tobacco products in Japan and evidence from other countries on exposure to tobacco advertising in unregulated channels. Pervasive global HTP marketing through prominent displays in convenience stores, duty-free stores, dedicated IQOS boutique stores, Internet and social media channels such as Instagram, Facebook, and Twitter and a spectrum of other youth-oriented events are well described in recent reviews [13,40,41]. Between 2017 and 2019, PMI reported a three-fold increase in the number of stand-alone IQOS stores worldwide from 63 to 199 and more than twice the number of retailers selling HTPs from 292 to 679 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some evidence that HTPs may involve some partial combustion [7], the tobacco industry argues that because HTPs do not involve combustion, they are potentially less harmful than combustible cigarettes [8][9][10]. While several independent studies have reported significantly lower emissions of some chemicals/toxicants from HTPs, it is not clear whether reduced exposure means reduced risk to HTP users [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%